Low-dose phase-based X-ray imaging techniques for in situ soft tissue engineering assessments. (March 2016) - Izadifar, Zohreh; Honaramooz, Ali; Wiebe, Sheldon; Belev, George; Chen, Xiongbiao; Chapman, Dean
Abstract: In tissue engineering, non-invasive imaging of biomaterial scaffolds and tissues in living systems is essential to longitudinal animal studies for assessments without interrupting the repair process. Conventional X-ray imaging is inadequate for use in soft tissue engineering due to the limited absorption difference between the soft tissue and biomaterial scaffolds. X-ray phase-based imaging techniques that derive contrast from refraction or phase effects rather than absorption can provide the necessary contrast to see low-density biomaterial scaffolds and tissues in large living systems. This paper explores and compares three synchrotron phase-based X-ray imaging techniques—computed tomography (CT)-diffraction enhanced imaging (DEI), -analyzer based imaging (ABI), and -phase contrast imaging (PCI)—for visualization and characterization of low-density biomaterial scaffolds and tissues in situ for non-invasive soft tissue engineering assessments. Intact pig joints implanted with polycaprolactone scaffolds were used as the model to assess and compare the imaging techniques in terms of different qualitative and quantitative criteria. For long-term in vivo live animal imaging, different strategies for reducing the imaging radiation dose and scan time—reduced number of CT projections, region of interest, and low resolution imaging—were examined with the presented phase-based imaging techniques. The results demonstrated promising capabilities of the phase-based techniques for visualization of biomaterial scaffolds and soft tissues in situ . The low-dose imaging strategies were illustrated effective for reducing the radiation dose to levels appropriate for live animal imaging. The comparison among the imaging techniques suggested that CT-DEI has the highest efficiency in retaining image contrast at considerably low radiation doses.